Policing in the Slovak Republic. The organization and current problems of police work - Gašpierik, Libor (Wydawnictwo Uniwersytetu Wrocławskiego, 2016)
The Police perform one of the most important roles within the modern society from the viewpoint of providing and maintaining peace, order and security. In the Slovak Republic the Police have been in existence for a relatively short time, but legislation regulating their activities and structure has already undergone several reforms. This treatise contains information regarding the structure and tasks of the Police of the Slovak Republic, discusses the development of criminality within the Slovak Republic, and analyses the current social status of the Police.
Keywords: policja budowlana; Republika Słowacji; bezpieczeństwo